Proton pump inhibitors in critically ill mechanically ventilated patients with COVID-19: protocol for a substudy of the Re-EValuating the Inhibition of Stress Erosions (REVISE) Trial - Dennis, Brittany B.; Thabane, Lehana; Heels-Ansdell, Diane; Dionne, Joanna C.; Binnie, Alexandra; Tsang, Jennifer; Guyatt, Gordon; Ahmed, Aijaz; Lauzier, François; Deane, Adam; Arabi, Yaseen; Marshall, John; et al. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Critically ill patients commonly receive proton pump inhibitors (PPIs) to prevent gastrointestinal (GI) bleeding from stress-induced ulceration. Despite widespread use in the intensive care unit (ICU), observational data suggest that PPIs may be associated with adverse outcomes in patients with COVID-19 infection. This preplanned study is nested within a large randomized trial evaluating pantoprazole versus placebo in invasively ventilated patients. The 3 objectives are as follows: (1) to describe the characteristics of patients with COVID-19 in terms of demographics, biomarkers, venous thromboembolism, tracheostomy incidence and timing, and other clinical outcomes; (2) to evaluate the impact of COVID-19 infection on clinically important GI bleeding, 90-day mortality, and other outcomes compared to a propensity-matched non-infected cohort; and (3) to explore whether pantoprazole has a differential treatment effect on clinically important GI bleeding, 90-day mortality, and other outcomes in patients with and without COVID-19 infection. Methods The ongoing trial Re-EValuating the Inhibition of Stress Erosions (REVISE) compares pantoprazole 40 mg IV to placebo on the primary efficacy outcome of clinically important GI bleeding and the primary safety outcome of 90-day mortality. The protocol described in this report is for a substudy focused on patients with COVID-19 infection that was not in the original pre-pandemic trial protocol. We developed a one-page case report form to characterize these patients including data related to biomarkers, venous thromboembolism, COVID-19 therapies, tracheostomy incidence and timing, duration of mechanical ventilation, and ICU and hospital stay. Our analysis will describe the trajectory of patients with COVID-19 infection, a propensity-matched analysis of infected and non-infected patients, and an extended subgroup analysis comparing the effect of PPI among patients with and without COVID-19 infection. Discussion Prophylactic acid suppression in invasively ventilated critically ill patients with COVID-19 infection has unknown consequences. The results of these investigations will inform practice, guidelines, and future research. Trial registration REVISE Trial [NCT03374800 December 15, 2017], COVID-19 Cohort Study [NCT05715567 February 8, 2023].